Civilizational Deviation in Collective Mediation: A Comparative Analysis of the Cretan Question and the Nagorno-Karabakh Conflict - Aytekin, Cavit Emre; Okur, Mehmet Akif (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2024)
This study explores the phenomenon of civilizational deviation in collective mediation processes within international conflicts, where perceived civilizational identities significantly impact outcomes. Comparing the late 19th-century Cretan Question and the 1988-1994 Nagorno-Karabakh Conflict, it reveals how civilizational factors obstruct collective mediation processes. In both cases, conflicting parties held perceptions of civilizational proximity or distance to the collective mediators, diverting mediation process from established international peace frameworks. The mediation process in Crete failed to deter separatism driven by religious self-determination, resulting in a peace design incongruent with prevailing international peace framework (Richmond, Oliver P. 2022. The Grand Design: The Evolution of the International Peace Architecture. Oxford: Oxford University Press; 2021. Similarly, the OSCE Minsk Group's efforts in Nagorno-Karabakh faced challenges aligning with normative mandates from the UN peace framework. This analysis illuminates complexities in mediation influenced by civilizational perceptions and highlighting the need to address civilizational deviation for international peace.
Keywords: Civilizational deviation; collective mediation; international peace framework; Ottoman-Greek War of 1897; Nagorno-Karabakh dispute; PEACE; CONCERT; EUROPE; WAR; PEACEMAKING; RESOLUTION; RUSSIA; ISLAND; International Relations